Young geodynamic activity in the marginal fault zone of the Sudetic Block - new data - Wojewoda, Jurand; Wajs, Jarosław; Sokalski, Dominik (Geologos, 2024)
A quarter of a century ago, during cartographic works using then-known field methods for measuring structural features, on the boundary of the Sudetic and Fore-Sudetic blocks, new phenomena were recognised; these were interpreted to be tectonic in nature and the result of left-lateral strike-slip movement in the subsurface. Grabens, half-grabens, shear zones and seismites in the gold-bearing sands and gravels that form the slopes of the valley of the River Kaczawa, are estimated to be of Pliocene and early Pleistocene age, having been interpreted as deposits of the pre-Kaczawa alluvial fan system. The natural exposures documented 25 years age have now all disappeared. In 2022, these levels became exposed again as a result of renewed gravel exploitation and phenomena described in the past reappeared. Field measurements were made again, this time using modern data-recording techniques, such as photogrammetry and terrestrial laser scanning. This work has enabled a comparison of field measurement methods with those obtained from the point clouds data. The results were found to be highly consistent. At the same time, precise reconstructions of the structures and their connection to the geodetic reference system make it possible to supplement previous geokinematic interpretations for this segment of the Sudetic Marginal Fault Zone (SMFZ). A formerly postulated left-lateral strike-slip regime in this zone was confirmed during the period of formation of the pre-Kaczawa alluvial fan deposits, but also probable is a kinematic inversion that must have occurred during, or just after, the early Pleistocene.